Numerical Two-Dimensional Steady-State Evaluation of the Thermal Transmittance Reduction in Hollow Blocks - Marcelo Adriano Fogiatto; Gerson Henrique dos Santos; João Victor Reia Catelan (Energies, 2019)
After the first concerns about global energy consumption around the 70 s, some standards were established with the aim of improving the energy efficiency in buildings. In this context, according to the US Department of Energy, heating, ventilation, and air conditioning (HVAC) systems comprise about 50% of the building energy consumption and 20% of total consumption in the United States. Energy consumption of this kind of equipment depends on several factors, one of the most important factors being the heat transfer through the building envelope. In the walls, hollow concrete blocks have become common in recent years due to advantages such as their strength, their space for pipes and wiring, and fast construction, among others. In order to reduce the thermal load, several forms of insulation were tested on these constructive elements. Thus, effects of the low emissivity, insulating material, radiant shields, and baffles on the inner cavities of the blocks are presented in this paper. Effects of temperature differences between the exterior surfaces on the thermal transmittance and on the combined average heat transfer coefficient inside the cavities are also shown.